Mild fetal hydronephrosis indicating vesicoureteric reflux. Issue 2 (March 1994) - Marra, G; Barbieri, G; Moioli, C; Assael, B M; Grumieri, G; Caccamo, M L
Abstract : The management of neonates with mild hydronephrosis diagnosed antenatally is still debated. Although some of these infants are normal, it is recognised that others will have mild obstruction of the ureteropelvic junction or vesicoureteric reflux (VUR). A prospective study was performed in all newborn infants with an antenatal diagnosis of mild hydronephrosis (47 babies, 62 kidneys) born over a two year period in order to assess the frequency of VUR. Voiding cystography in 14 patients with 21 renal units showed VUR. Two patients underwent surgery and the VUR resolved; the other 12 received medical treatment. Repeat cystography was scheduled for 12-18 months later, when a high rate of spontaneous cure was observed. The remaining patients were monitored by ultrasonography but only in one case did hydronephrosis deteriorate because of the presence of severe ureteropelvic junction obstruction. It is concluded that mild dilatation of the pelvis might be an expression of a potentially severe malformation such as VUR, and a careful follow up of these cases is mandatory.